2020
DOI: 10.1186/s12245-020-00277-x
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of and attitudes towards cardiopulmonary resuscitation among junior doctors and medical students in Upper Egypt: cross-sectional study

Abstract: Background: Cardiopulmonary resuscitation (CPR) is a fundamental skill that should be acquired by all medical community members. This study aims to evaluate the knowledge and attitudes of junior doctors and medical students towards CPR and CPR training at Beni-Suef University Hospital in Upper Egypt, a representative region with conditions common to LMIC settings. Participants and methods: In this cross-sectional study, a total of 205 participants (60 junior doctors and 145 medical students) responded to a sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
20
0
3

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 12 publications
5
20
0
3
Order By: Relevance
“…A study by Mohamad et al on junior doctors showed that 68.3% did not have sufficient knowledge to perform resuscitation, including CPR. 24 This is in line with our findings where junior EHCW of fewer than 4 years LOS had lower knowledge compared to their senior colleagues.…”
Section: Discussionsupporting
confidence: 90%
“…A study by Mohamad et al on junior doctors showed that 68.3% did not have sufficient knowledge to perform resuscitation, including CPR. 24 This is in line with our findings where junior EHCW of fewer than 4 years LOS had lower knowledge compared to their senior colleagues.…”
Section: Discussionsupporting
confidence: 90%
“…It was indicating that the respondents' knowledge of CPR was inadequate. Similar knowledge deficiencies were found among medical students in other developing countries, Jordan (Oteir et al, 2019), India (Aroor et al, 2014, Egypt (Mohammed et al, 2020). Lack of continuous and formal training may be the main reason for the lack of CPR knowledge among medical students in developing countries.…”
Section: Discussionsupporting
confidence: 57%
“…In India, one study found that about 19% of medical students received training [ 8 ]. Similarly, BLS training was reported to be inadequate among undergraduate students in Pakistan [ 7 ], Ethiopia [ 18 ], Nigeria [ 9 ], and Egypt [ 19 ]. On the other hand, in the USA, BLS training was recommended for every healthcare giver since 1966 [ 20 ], and most UK medical colleges offer BLS training [ 21 ].…”
Section: Discussionmentioning
confidence: 99%